Copper in agricultural fields and in crops - a review (The Journal of Building and Land Development, 2018)
It is important to understand chemical behaviour of copper in soils so as to comprehend different ways of immobilizing it and avoiding the contamination of the food web. This paper focuses on copper contamination in agricultural soils and in crops grown on copper contaminated soils. Solubility, mobility and bioavailability of copper under different soil conditions as a tool of assessing risks associated with utilization of copper contaminated soils have been discussed. Feasible options that can be used to immobilise/attenuate copper toxicity in soils have been proposed. The presence of elevated concentrations of copper in soils pose ecological risks, therefore, soluble copper should be converted to less soluble fractions. This can be achieved through leaving the land fallow for a long time so as to give soluble copper fractions enough time to change to insoluble fractions. Understanding chemical properties of organic amendments that are added to soils as fertilizers is crucial for avoiding eventual copper mobilization and contamination in soils. The amendments that have a potential of immobilizing copper can be applied on copper contaminated soils as a remedial option. It is recommended to avoid organic amendments that contain elevated levels of copper contents like pig manure.Key words: contamination, coffee, soils, bioavailability, mobility